A new species of Ceropegia (Apocynaceae) from northern Kerala, India - Biju, P.; Josekutty, E.j.; Kambale, S.s.; Augustine, J.; Bruyns, P.v. (Phytotaxa, 2020)
A new species, Ceropegia ariyittaparensis P.Biju et al. is described from the low-lying lateritic plateaux of northern Kerala, SW India. This species belongs to Ceropegia sect. Tiloris H.Huber. It is most similar to Ceropegia vartakii (Kambale & S.R.Yadav) Bruyns, but differs by its elongated buds, maroon, longitudinally folded and lanceolate corolla-lobes, its taller outer coronal lobes and longer connivent inner coronal lobes, which rise in a short column above the style-head.